2003
DOI: 10.1007/s00464-002-8901-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open donor nephrectomy

Abstract: LapDN offers improved QOL at lower costs, despite the fact that this analysis included patients treated during the learning curve of LapDN at our institution. By potentially increasing organ donor rates, LapDN may be further cost saving by decreasing the number of patients receiving dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…However, there are concerns that the laparoscopic technique results in increased costs due to the requirement of expensive disposable equipment such as tro- cars, hand ports, and vessel staplers. In fact, cost-effectiveness of laparoscopic DN is discussed controversially as the hospital stay needs to be shortened to balance the increased cost for the surgical procedure and longer operating times (3,4,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are concerns that the laparoscopic technique results in increased costs due to the requirement of expensive disposable equipment such as tro- cars, hand ports, and vessel staplers. In fact, cost-effectiveness of laparoscopic DN is discussed controversially as the hospital stay needs to be shortened to balance the increased cost for the surgical procedure and longer operating times (3,4,10).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, DN was performed routinely via lumbal incision with or without rib resection. Until today, many alternative surgical strategies to obtain kidneys from living donors have been described such as the retroperitoneoscopic and laparoscopic approach (1)(2)(3)(4). However, the laparoscopic technique is frequently associated with long operating times and higher cost for surgical equipment such as trocars, hand ports, and vessel staplers.…”
mentioning
confidence: 98%
“…Higher salaries would further offset the initial financial disadvantages of LDN. Furthermore, an advisory organ of the Dutch Ministry of Finance recently reported that treatments costing up to €80,000 (about $96,000) per QALY may be acceptable (19). In the United Kingdom, the acceptable threshold equals about €50,000 (15).…”
Section: Discussionmentioning
confidence: 99%
“…This explains why the difference in QOL appears smaller than the differences between the groups with regard to the SF-36. The conversion of QOL in QALYs has been debated, but current guidelines in the Netherlands advise quantification of QOL in QALYs (19). The main advantage of this conversion into QALYs is that the gain of a therapy allows comparison to the gain of other therapies (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic procedures are attractive for patients due to reduced pain, shorter postoperative hospital stays, faster returns to preoperative function and better cosmetic results [1,2,3,4]. Despite these benefits, laparoscopic procedure produces adverse effects on splanchnic organs secondary to intraabdominal pressure.…”
Section: Introductionmentioning
confidence: 99%